Marine Vertical Gravity Gradients Reveal the Global Distribution and Tectonic Significance of "Seesaw" Ridge Propagation. Issue 2 (16th February 2021) - Harper, Hugh; Tozer, Brook; Sandwell, David T.; Hey, Richard N.
Abstract: The segmentation of mid‐ocean ridges is a defining characteristic of seafloor spreading, yet some tectonic processes operating at segment boundaries remain poorly understood. Here, we analyze new satellite‐derived vertical gravity gradient (VGG) data, which reveal an abundance of off‐axis seafloor features that are oblique to ridges and transform faults and thus reflect the occurrence of ridge propagation at some segment boundaries. However, unlike many propagating ridges, these features commonly reverse direction leaving W‐shaped signatures in the seafloor which we refer to as "seesaw propagators" (SSPs). Using the VGG, we have documented these globally and find that: (1) SSPs are ubiquitous on seafloor that formed at half spreading rates between 10 and 40 mm year −1 and their total length is about 1/3 that of fracture zones. (2) The lithospheric age offset across SSPs (0–2.5 Ma) is less than transform faults (2–10 Ma), which likely reflects a rheological threshold, whereby only young and weak lithosphere allows for "non‐rigid" SSP behavior. (3) Isostatic modeling of well‐surveyed SSPs confirms that they formed on young and thin (3 km) lithosphere. (4) The directional changes of SSPs in both time and space appear largely uncorrelated and cannot be explained by previous regional‐scale models invoked to explain unidirectional ridge propagation and thus require a different driving force. Key Points: The process of "seesaw" ridge propagation is ubiquitous on seafloor that forms at half spreading rates between 10 and 40 mm yr −1 Globally, the total length of seesaw propagators is approximately one‐third that of fracture zones Driving mechanisms previously proposed to explain unidirectional ridge propagation fail account for the behavior of seesaw propagators